Molecular Docking Study on the Interaction of Riboflavin (Vitamin B2) and Cyanocobalamin (Vitamin B12) Coenzymes. (31st March 2013) - Hafeez, Ambreen; Saify, Zafar Saied; Naz, Afshan; Yasmin, Farzana; Akhtar, Naheed
Abstract : Cobalamins are the largest and structurally complex cofactors found in biological systems and have attracted considerable attention due to their participation in the metabolic reactions taking place in humans, animals, and microorganisms. Riboflavin (vitamin B2 ) is a micronutrient and is the precursor of coenzymes, FMN and FAD, required for a wide variety of cellular processes with a key role in energy-based metabolic reactions. As coenzymes of both vitamins are the part of enzyme systems, the possibility of their mutual interaction in the body cannot be overruled. A molecular docking study was conducted on riboflavin molecule with B12 coenzymes present in the enzymes glutamate mutase, diol dehydratase, and methionine synthase by using ArgusLab 4.0.1 software to understand the possible mode of interaction between these vitamins. The results from ArgusLab showed the best binding affinity of riboflavin with the enzyme glutamate mutase for which the calculated least binding energy has been found to be −7.13 kcal/mol. The results indicate a significant inhibitory effect of riboflavin on the catalysis of B12 -dependent enzymes. This information can be utilized to design potent therapeutic drugs having structural similarity to that of riboflavin.